2004
DOI: 10.1111/j.0023-9216.2004.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Judging Police Misconduct: “Street-Level” versus Professional Policing

Abstract: In their interactions with citizens, police officers are prohibited from (1) using unnecessary Force, (2) Abusing their authority, (3) speaking Discourteously, or (4) using Offensive language, all captured by the acronym FADO. However, acts of police misconduct are complex social phenomena that involve both following legal guidelines and responding to extralegal or mitigating circumstances. Using a factorial survey of police-civilian interactions that introduce various dimensions of FADO and surrounding circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…While these descriptions may seem subtle, this study settled on using unnecessary force in vignettes, and the types of unnecessary force used here have a foundation in both the empirical and theoretical literature on the topic. Serone et al (2004) describe offensive language as a minor type of verbal force that other officers may consider unnecessary. A minor form of physical force, slapping the suspect once in the back of the head, is considered unnecessary force at an intermediate level.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…While these descriptions may seem subtle, this study settled on using unnecessary force in vignettes, and the types of unnecessary force used here have a foundation in both the empirical and theoretical literature on the topic. Serone et al (2004) describe offensive language as a minor type of verbal force that other officers may consider unnecessary. A minor form of physical force, slapping the suspect once in the back of the head, is considered unnecessary force at an intermediate level.…”
Section: Independent Variablesmentioning
confidence: 99%
“…A minor form of physical force, slapping the suspect once in the back of the head, is considered unnecessary force at an intermediate level. Police administrators consider slapping to be unnecessary and more serious than offensive language (Serone et al 2004). Patrol officers may not consider slapping a suspect in the back of the head unacceptable if they believe the suspect's behavior justified or warranted this action.…”
Section: Independent Variablesmentioning
confidence: 99%
“…While some studies have shown that the public believes force is sometimes necessary, citizens have also expressed concern over the use and overuse of coercive measures as a police tactic (Paoline et al 2000;Seron et al 2004;Vaughn 1996). As more communities adopt a community policing approach, which emphasizes a change in the role of law enforcement to one focused on problem solving and preventative approaches as ways to stop crime and conflicts, the necessity of force is under renewed scrutiny (Engel and Worden 2003).…”
Section: Review Of Literaturementioning
confidence: 99%
“…These ''negative'' incidents ranged from police acting disrespectful, rude, in an inappropriate manner, engaging in harassment, and denying services to victims, to officers acting as the actual perpetrators of anti-LGBT verbal harassment, intimidation, and physical assault. There is debate within public opinion as well as literature on policing and police behavior as to the appropriate use of force particularly when officers encounter a dangerous situation (Seron et al 2004;Terrill et al 2003). This was taken into consideration when cases were rated using callers' experiences.…”
Section: Contact With Policementioning
confidence: 99%
“…In answering questions as why law enforcement officers engage in bribery, researchers (Seron, 2004;Maher, 2008;) have identified minimum education as a cause of misbehavior. While other researchers (Kane, 2002;Weitzer & Tuch, 2004;Lersch, bazley, Mieczkowski & Childs, 2008;Ivkovic, 2009;) mentioned race as an antecedent of misbehavior followed by Schafer (2010) and Gordon (2010) found ineffective leadership is also a cause of misbehavior.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%